Long-term risk of ischemic heart disease after adjuvant radiotherapy in breast cancer: results from a large population-based cohort - Wennstig, Anna-Karin (Breast Cancer Res, 2020)
BACKGROUND: Adjuvant radiotherapy (RT) for breast cancer (BC) has been associated with an increased risk of ischemic heart disease (IHD). We examined the incidence of IHD in a large population-based cohort of women with BC. METHODS: The Breast Cancer DataBase Sweden (BCBaSe) includes all women diagnosed with BC from 1992 to 2012 (n = 60,217) and age-matched women without a history of BC (n = 300,791) in three Swedish health care regions. Information on comorbidity, educational level, and incidence of IHD was obtained through linkage with population-based registries. The risk of IHD was estimated by Cox proportional hazard regression analyses and cumulative incidence by the Kaplan-Meier method. RESULTS: Women with BC had a lower risk of IHD compared to women without BC with a hazard ratio (HR) of 0.91 (95% CI 0.88–0.95). When women with left-sided BC were compared to right-sided BC, an increased HR for IHD of 1.09 (95% CI 1.01–1.17) was seen. In women receiving RT, a HR of 1.18 (95% CI 1.06–1.31) was seen in left-sided compared to right-sided BC, and the HRs increased with more extensive lymph node involvement and with the addition of systemic therapy. The cumulative IHD incidence was increased in women receiving left-sided RT compared to right-sided RT, starting from the first years after RT and sustained with longer follow-up. CONCLUSIONS: Women given RT for left-sided BC during 1992 to 2012 had an increased risk of IHD compared to women treated for right-sided BC. These women were treated in the era of three-dimensional conformal RT (3DCRT), and the results emphasize the importance of further developing and implementing RT techniques that lower the cardiac doses, without compromising the beneficial effects of RT.